2024
DOI: 10.3389/fmars.2024.1346275
|View full text |Cite
|
Sign up to set email alerts
|

Clogging risk of microplastics particles in porous media during artificial recharge: a laboratory experiment

Huan Wang,
Junjie Zhang,
Yudao Chen
et al.

Abstract: Management aquifer recharge (MAR) technology is widely applied to solve seawater intrusion caused by groundwater overexploitation in coastal areas. However, MAR creates an important pathway for microplastics (particle size< 5 mm) to enter groundwater. To explore the clogging potential of microplastics in aquifer media, a series of laboratory-scale column experiments were conducted in this study. The hydraulic conductivity of porous media and deposition amount of microplastics were investigated under dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
0
0
0
Order By: Relevance
“…It has been shown that Darcy’s law can be used to analyze the migratory movement of MPs in saturated porous media under specific conditions. Wang et al [ 42 ] used Darcy’s law to calculate the variation of hydraulic conductivity and then analyzed the permeability of MPs with different particle sizes and the clogging mechanism, which proved its applicability in predicting the migration and distribution of MPs in similar environments.…”
Section: Migration Mechanism Of Mps In Porous Mediamentioning
confidence: 99%
“…It has been shown that Darcy’s law can be used to analyze the migratory movement of MPs in saturated porous media under specific conditions. Wang et al [ 42 ] used Darcy’s law to calculate the variation of hydraulic conductivity and then analyzed the permeability of MPs with different particle sizes and the clogging mechanism, which proved its applicability in predicting the migration and distribution of MPs in similar environments.…”
Section: Migration Mechanism Of Mps In Porous Mediamentioning
confidence: 99%